Changes in evapotranspiration and phenology as consequences of shrub removal in dry forests of central Argentina - Marchesini, Victoria Angela (2015)
More than half of the dry woodlands (forests and shrublands) of the world are in South America, mainly in Brazil and Argentina, where in the last years intense land use changes have occurred. This study evaluated how the transition from woody-dominated to grass-dominated system affected key ecohydrological variables and biophysical processes over 20 000 ha of dry forest in central Argentina. We used a simplified surface energy balance model together with moderate-resolution imaging spectroradiometer–normalized difference vegetation index data to analyse changes in above primary productivity, phenology, actual evapotranspiration, albedo and land surface temperature for four complete growing seasons (2004–2009). The removal of woody vegetation decreased aboveground primary productivity by 15–21%, with an effect that lasted at least 4 years, shortened the growing season between 1 and 3 months and reduced evapotranspiration by as much as 30%. Albedo and land surface temperature increased significantly after the woody to grassland conversion. Our findings highlight the role of woody vegetation in regulating water dynamics and ecosystem phenology and show how changes in vegetative cover can influence regional climatic change.